Analysis of the main antioxidant enzymes in the roots of Tamarix ramosissima under NaCl stress by applying exogenous potassium (K+) - Chen, Yahui; Li, Haijia; Zhang, Shiyang; Du, Shanfeng; Zhang, Jinchi; Song, Zhizhong; Jiang, Jiang (Frontiers in Plant Science, 2023)
More than 25% of the world's arable land is affected by soil salinization, and the halophyte Tamarix ramosissima Ledeb (T. ramosissima), known as the representative of Tamarix plants, are widely grown in salinized soil. However, the mechanism of antioxidative enzyme activity of potassium (K+) as an essential element for plant growth in alleviating the damage of NaCl stress to it is less reported. In this study, we observed changes in root growth at 0h, 48h and 168h of T. ramosissima, performed antioxidant enzyme activity assay, transcriptome sequencing and non-targeted metabolomic analysis were processed to understand changes in their roots and the changes in the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT). Candidate differentially expressed genes (DEGs) and differential metabolites related to the activities of major antioxidant enzymes were mined and further verified by quantitative real-time PCR (qRT-PCR). As the time increased, the results showed that compared with the 200 Mm NaCl group, the root growth of the 200 mM NaCl + 10 mM KCl group increased, the activities of SOD, POD and CAT increased the most, but the contents of hydrogen peroxide (H2O2) and Malondialdehyde (MDA) increased less. Meanwhile, 58 DEGs related to SOD, POD and CAT activities were changed during the application of exogenous K+ for 48h and 168h in T. ramosissima. Based on association analysis of transcriptomic and metabolomic data, we found coniferyl alcohol, which can act as a substrate to label catalytic POD. It is worth noting that Unigene0013825 and Unigene0014843, as POD-related genes, have positively regulated the downstream of coniferyl alcohol, and they have a significant correlation with coniferyl alcohol. In summary, 48h and 168h of exogenous K+ applied to the roots of T. ramosissima under NaCl stress can resist NaCl stress by scavenging the reactive oxygen species (ROS) generated by high salt stress by enhancing the mechanism of antioxidant enzyme activity, relieving NaCl toxicity and maintaining growth. This study provides genetic resources and a scientific theoretical basis for further breeding of salt-tolerant Tamarix plants and the molecular mechanism of K+ alleviating NaCl toxicity.